Дослідження детермінованих факторів робочої зони - Березуцька, Н. Л.; Халіль, В. В.; Березуцький, В. В.; Глива, В. А. (RS Global, 2017)
The paper considers the approaches to the European integration of the normative acts of Ukraine, regarding the implementation of the standards of social responsibility which concern the issues of occupational risks and their reduction in the workplace. Studies of the state of the deterministic factors of the working zone on the complex, in terms of their working conditions, the production of the machine-building industry are given. Approaches are proposed to solve these problems in modern conditions of domestic production
Keywords: risks; management; security; deterministic factors standards; audit